Antigen-presenting capacity of rheumatoid synovial fibroblasts - Boots, A M; Wimmers-Bertens, A J; Rijnders, A W (Immunology, 1994)
In normal, healthy joints, synovial fibroblasts do not express major histocompatibility complex (MHC) class II molecules. However, in inflamed joints of rheumatoid arthritis (RA) patients, synovial fibroblasts show an abundant expression of MHC class II. Does this increase in expression have functional consequences for antigen presentation to T cells? To date, the precise role of synovial fibroblasts in antigen presentation has not been documented. Here, we show by three different examples that cultured synovial fibroblasts with interferon-gamma (IFN-gamma)-induced MHC class II expression are capable of processing soluble protein for presentation to CD4+ T cells. First, the antigen-presenting cell (APC) function of synovial fibroblasts was studied in an autologous model. From synovial tissue of a RA patient both a fibroblast cell line and a tetanus toxoid (TT)-specific CD4+ T-cell line were generated. A dose-dependent TT response was observed only when TT was presented by IFN-gamma-pretreated synovial fibroblasts. As more direct evidence for MHC class II-restricted antigen presentation, the response of a Mycobacterium tuberculosis-specific CD4+ T-cell clone isolated from rheumatoid synovial fluid was demonstrated in the presence of synovial fibroblasts. The response was DR4Dw4-restricted and could be inhibited by monoclonal antibody (mAb) to HLA-DR. In addition, the lymphokine secretion pattern of the synovial T-cell clone did not differ qualitatively upon antigen-specific stimulation using peripheral blood mononuclear cells (PBMC) or synovial fibroblasts as APC. In order to provide evidence for intracellular antigen processing we next examined the response of a M. leprae-specific T-cell clone with known epitope specificity. Our data suggest that synovial fibroblasts are not passive bystanders, but can become active participants in the development and maintenance of chronic inflammation.